Rheological properties and optimal spray drying process parameters of Piper betle L. (betel) leaf extracts coated with different excipients - Tee, Lee Hong (2011)
Piper betle L., more commonly known as betel or local name of Sirih, belongs to the family Piperaceae. Previous research has shown that the leaves of P. betle possess tremendous beneficial effects including antimicrobial, antioxidant, anti-diabetic,wound healing and gastro-protective properties. The presence of these beneficial properties indicates that leaf extract of betel has great potential for development into a wide range of health food supplements. However, there is a lack of research on the processing aspects to produce its bioactive component. This research studied two main aspects including the rheological properties of betel leaves extract and optimization of spray drying process coated with three excipients which were xanthan gum, maltodextrin and lactose. The main purpose for studying the rheological properties of betel leaves is to prepare data that would be useful in designing processing equipment for betel leaves extract products. Spray drying was chosen for easy handling and the preservation of bioactive compounds. The process parameters of spray drying were inlet hot air temperature, feed flow rate or pump flow rate and aspirator rate. The properties of dried powder produced were investigated in terms of particle size distribution, moisture content and bioactive component; hydroxychavicol (HC) content, hygroscopicity and powder yield. The experimental run and optimization work were designed using Box-Behnken method of Response Surface Methodology (RSM). Proximate analysis on Piper betle L. freeze-dried extract was successfully conducted. The compositions consist of 16.45% moisture, 28.18% ash, 9.36% protein, 0.11% crude fiber, 0.16% crude fat and 45.74% carbohydrate. Rheology behavior of 10 °Brix and 12 °Brix concentration of betel leaves extract at temperature 5, 10, 20, 30, 40 and 50 °C was successfully investigated. Bingham Plastic Model and Casson model illustrated that betel leaves extract showed a plastic behavior. Power Law model was suitable to represent the rheology model of betel leaves extract. The optimum operation conditions for the highest hydroxychavicol content with the lowest moisture content and the smallest particle size for xantham gum-coated powder were obtained at inlet drying temperature of 160 ˚C, the pump flow rate of 3 rpm, and airflow rate of 86%. The optimum responses of the process were: moisture content of 10.14%, particle size distribution of 7.37 μm, powder yield of 6.72 g,powder hygroscopicity of 26.76 g/100g dry powder and HC content of 383.19 ppm. For maltodextrin-coated spray drying process, the optimum processing parameters were as follow: the inlet drying temperature of 159.53˚C, the pump flow rate of 6.13 rpm, and airflow rate of 98.33%. The optimum responses of the process were:moisture content of 6.99%, particle size distribution of 5.48 μm, powder yield of 10.53 g, powder hygroscopicity of 28.88 g/100g dry powder and HC content of 229.33 ppm. While for lactose-coated spray drying process, the optimum processing parameters were as follow: the inlet drying temperature of 160 ˚C, the pump flow rate of 5.33 rpm, and airflow rate of 100%. The optimum responses of the process were: moisture content of 6.96%, particle size distribution of 6.58 μm, powder yield of 16.54 g, powder hygroscopicity of 16.58 g/100g dry powder and HC content of 80.23 ppm. Xantham gum was found out to be the most suitable carrier for the spray drying process of betel leaves extract as it contained the highest amount of HC content and showed better morphological properties which are more spherical in shape, more consistent in size and less shrinkage present on the surface of the particle.